Perubahan Sosial Masyarakat Desa Sundutan Tigo - Nasution, Toni; Yoana, Lesma; Fazryn, Isnainy; Haliza, Salmia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In a society that experiences symptoms of changes in social and cultural conditions, it is called socio-cultural change. Symptoms of changing social conditions always occur in a society. This research was conducted to: 1) Describe the environmental conditions in the village of Sundutan Tigo. 2) describes community activities such as community social activities caused by the advancement of science and technology. 3) describe what causes the social culture of society to change within the scope of science and technology progress. 4) describe what has arisen from socio-cultural changes for the Sundutan Tigo community. The data we collect through data complementary documents such as books, journals, articles and other literature related to this research. The results of this study are: 1) In Sundutan Tigo Village there is local wisdom, namely a community tradition in which there are values, which have been carried out from generation to generation and have changed. Advances in science and technology in the form of ideas and activities about the relationship between humans and God, as well as the environment. 2) good social relations are seen as important in society to maintain harmony. 3) there are factors that cause and the impact that occurs from social changes that result in things that are not the same in the current socio-cultural conditions with the previous year. Keywords: Socio-Cultural Change, Village Communities, Sundutan Tigo Village, Science and Technology.